Development Scenarios of Foreign Economic Activity of Large Russian Industrial Regions (On the Example of The South Urals) - Irina Y. OKOLNISHNIKOVA; Antonina I. UKHOVA; Margarita D. OKOLNISHNIKOVA; Mark S. ANASTASOV (Communications of International Proceedings, 2020)
The article is devoted to the study of ways to improve the foreign economic activity of large industrial regions of Russia. The authors describe the main factors hindering the development of export potential and reveal the tools for solving this problem. The article presents the forecast of the development of foreign economic activity of the Chelyabinsk region for the period up to 2035, compiled by the authors, using the methods of expert assessments and economic and mathematical modeling, in three versions - conservative, basic and target. This forecast was compiled by the authors taking into account the main scenarios of the socio-economic development of Russia and fully takes into account the specific features of the development of the Russian and regional economies. The authors propose sectors of the economy that are promising for the expansion of foreign trade and give forecasts for the development of the region's export potential.
Keywords: Regional Economy; Foreign Economic Activity; Export Operations; Marketing Strategies for The Development of The Region.